Access to justice: the human dignity of Muslim and women divorce in Malaysia - Kamaruddin, Zaleha (IIUM Press and IIMU, 2009)
Despite the fact that the aim of the Shari'ah is to establish a healthy family unit through marriage, Islam does recognise divorce. Divorce is, however, couched in the context of important moral and human principles. Islam commands husbands and wives to consort with each other with kindness or to part from each other with kindness. Divorce should not be a weapon llsed against spouses, but a humane practice which is resorted to in exceptional circumstances; i.e. when it is feared that the limit set by Allah SWT will be transgressed. Notwithstanding Qur'anic affirmation of equality and justice, rationality and strong moral exhortation, women are suffering at the expense of men's abuse of divorce laws. Despite reforms in legislation which has been passed in the majority of Muslim countries to correct abuses in Muslim society, there is widespread exploitation of divorce laws, and Malaysia is no exception.